Risk of Cardiovascular and Cerebrovascular Events in Polycystic Ovarian Syndrome Women: A Meta-Analysis of Cohort Studies - Zhang, Jun; Xu, Ji-Hong; Qu, Qian-Qin; Zhong, Guo-Qing (Frontiers in Cardiovascular Medicine, 2020)
Aim: This systematic review and meta-analysis aimed to investigate the risk of cardiovascular disease (CVD) and cerebrovascular disease (CeVD) events in women with polycystic ovary syndrome (PCOS). Methods: We searched the literatures in Pubmed, Embase, and Web of Science to identify the cohort studies reporting the association between PCOS and CVD/CeVD events from 1964 to June 1, 2020. Outcome variables such as all-cause mortality, cardiovascular death, any cardiovascular diseases, myocardial infarction, ischemic heart disease, and stroke are extracted from the identified literatures and reported the outcomes of the association in hazard ratios (HR) and odds ratios (OR). Results: Ten cohort studies comprising 166,682 samples are included in the review. Compared to non-PCOS women, the pooled risk of CVD events in PCOS women OR: 1.62 (95% CI: 1.34–1.97). In addition, the risk of myocardial infarction (OR: 2.57, 95% CI: 1.37–4.82), ischemic heart disease (OR: 2.77, 95% CI: 2.12–3.61), and stroke (OR: 1.96, 95% CI: 1.56–2.47) are higher in the PCOS group. However, no significant difference in the overall mortality (HR: 1.04, 95% CI: 0.57–1.86) and CVD-related death (HR: 1.49, 95% CI: 0.99–2.23) was observed. Funnel plots of all outcomes were roughly symmetric, and no significant publication bias was found. Conclusion: Through this study identified an increased risk of CVD and CeVD among women with PCOS including occurance of myocardial infarction, ischemic heart disease, and stroke, but no difference in the all cause or CVD related mortality observed. Further large scale studies are warranted to strengthen the association between PCOS and CV events.